Moral Attitudes Toward Pharmacological Cognitive Enhancement (PCE): Differences and Similarities Among Germans With and Without PCE Experience - Pohl, Sabine; Boelsen, Hannes; Hildt, Elisabeth (Frontiers in Pharmacology, 2018)
Pharmacological cognitive enhancement (PCE), the use of illicit and/or prescription drugs to increase cognitive performance, has spurred controversial discussion in bioethics. In a semi-structured interview study with 60 German university students and employees, differences and similarities in moral attitudes toward PCE among 30 experienced participants (EPs) vs. 30 inexperienced participants (IPs) were investigated. Substances EPs used most often are methylphenidate, amphetamines, tetrahydrocannabinol and modafinil. Both EPs and IPs addressed topics such as autonomous decision making or issues related to fairness such as equality in test evaluation and distortion of competition. While most EPs and IPs were convinced that the decision of whether or not to use PCE is part of their individual freedom, their views varied considerably with regard to fairness. IPs considered issues related to fairness as much more critical than EPs. Thus, a person’s moral attitudes toward PCE may not only depend on moral common sense, but also on whether they have used illegal and/or prescription drugs for PCE before. This points to the importance of including the various relevant stakeholder perspectives in debates on the ethical and social implications of PCE.